VIOLENCE EXPERIENCED BY FEMALE BRAZILIAN IMMIGRANTS IN PORTUGAL - Oliveira, Eliany Nazaré (2017)
This study aimed to analyze the violence experienced by female Brazilian immigrants  in Portugal. Conducted in the first half of 2016 with 682 women over 18 years in Portugal. Two types of data collection were introduced, online by the Limasurvey Platform and in person at the Consulates General of Brazil in Porto and Lisbon and the “Mais Brasil” association.  Psychological violence appeared in a larger proportion, family and friends were the main sought support. The marital status does not influence the violence suffered. The residence time in the country had an influence on the types of offenders. Believed to be crucial to create a policy that aims transformation actions aimed at strengthening public and collective consciousness of these female immigrants in the host country.